The Biological Effect of Synthesized Zinc Oxide Nanoparticles on Organic Pollutions in Drinking Water - Hussain, H. M.; Mahmood, M. B.; Yaaqoob, L. A. (Iraqi Journal of Science, 2024)
This study aimed to demonstrate the biosynthesis procedure of zinc oxide nanoparticles (Zn-O NPs) by using extracellular components from environmental isolates of Escherichia coli as reducing and stabilizing agent by adding 1 g of zinc sulfate to 10 ml of bacterial extract to prepare of zinc oxide nanoparticles. These organic pollutants are considered one of the most important causes of poisoning that have great health risks to humans and are also considered one of the most dangerous environmental pollutants as they are toxic and harmful to the environment. The optimum condition for Zn-O biosynthesis was characterized through several devices and techniques such as ultraviolet- visible (UV-Vis) Atomic force microscope (AFM) X-Ray diffractometer (XRD) Fourier Transform Infrared spectroscopy (FTIR) and field emission scanning electron microscopy (FE-SEM). In particular, a cutoff phenomenon of the biological synthesized Zn-O was found at around 325 nm using UV-Vis, while spherical shape particles were noticed using FE-SEM techniques. Also, the results of the AFM analysis revealed that Zn-O NPs have an average diameter of 37.15 nm. Determining the FTIR spectrum of the biosynthesized Zn-O nanoparticles showed Zn-O at the broad peak at 694.33 cm.